ANALISIS FAKTOR-FAKTOR KEPUTUSAN PEMBELIAN PRODUK AIR MINUM DALAM KEMASAN STUDI KASUS KONSUMEN AMDK SUKABELA DI KABUPATEN SEMARANG - Juwitasari, Desta Ewika Ayu; Handriani, Eka; Supraptini, Nunuk (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
Increasingly advanced business developments have resulted in increasingly fierce competition in the business world, therefore companies are always trying to increase market share and reach new customers. Basically, the more competitors, the more choices for consumers to choose products that match their expectations. So that from these changes, consumers become more careful in choosing new products that are launched. The purpose of this research is to determine the factors of purchasing decisions for packaged drinking water products in case studies of voluntary drinking water consumers in Semarang district. The type of research used is explanatory research. The population in this study is the entire population in this study are people who have bought AMDK Sukabela products in Semarang Regency. Using the sampling technique used, namely the alternative formula Lemeshow (1997), a sample of 96 respondents was obtained. The results of multiple regression analysis for the price variable on purchasing decisions obtained tcount 3.754, promotions on purchasing decisions obtained tcount 3.036 and distribution channels on purchasing decisions obtained tcount 3.527. Based on the Fcount test, the Fcount value is 41,926. The results of the study can be concluded that the variable price, promotion and distribution channels have a partial effect. Price, promotion and distribution channel variables simultaneously influence purchasing decisionsKeywords: Price, Promotion and Distribution Channels on Purchasing Decisions